Effects of naloxegol on whole gut transit in opioid‐naïve healthy subjects receiving codeine: A randomized, controlled trial - Halawi, H.; Vijayvargiya, P.; Busciglio, I.; Oduyebo, I.; Khemani, D.; Ryks, M.; Rhoten, D.; Burton, D.; Szarka, L. A.; Acosta, A.; Camilleri, M. (Neurogastroenterology and motility, 2018)
Background Nausea, vomiting, and constipation (OIC) are common adverse effects of acute or chronic opioid use. Naloxegol (25 mg) is an approved peripherally active mu‐opiate opioid receptor antagonist. Aim To compare the effects on pan‐gut transit of treatment with codeine, naloxegol, or combination in healthy volunteers. Methods We conducted a randomized, double‐blind, placebo‐controlled, single‐center, parallel‐group study in 72 healthy opioid‐naïve adults, randomized to: codeine (30 mg q.i.d.), naloxegol (25 mg daily), codeine and naloxegol, or matching placebo. During 3 days of treatment, we measured gastric emptying (GE) T1/2, colonic filling at 6 hours (CF6), colonic geometric center at 24 and 48 hours, and ascending colon emptying (ACE) T1/2. Key Results Participants were 59.7% women, median BMI 25.0 kg/m2, and median age 33.8 years. Codeine significantly retarded GE T1/2, CF6, overall colonic transit, and ACE T1/2. There was significant difference (P = .026) in GE T1/2 between codeine (144.0 min [IQR 110.5‐238.6]) and naloxegol (95.5 min [89.1‐135.4]). There was a significant overall group difference in CF6 (P = .023), with significant difference (P = .019) between codeine (11.0% [0.0‐45.0]) and naloxegol (51% [18.8‐76.2]). However, no significant differences were found between codeine‐treated participants concomitantly receiving placebo or naloxegol. Conclusions and Inferences Short‐term administration of naloxegol (25 mg) in healthy, opioid‐naïve volunteers does not reverse the retardation of gastric, small bowel, or colonic transit induced by acute administration of codeine. Further studies with naloxegol at higher dose are warranted to assess the ability to reverse the retardation of transit caused by acute administration of codeine in opioid‐naïve subjects. Nausea, vomiting, and constipation are common adverse effects of acute or chronic opioid use. We compared the effects on pan‐gut transit of treatment with codeine, naloxegol, or combination in healthy opioid‐naïve volunteers. Short‐term administration of naloxegol (25 mg) in healthy, opioid‐naïve volunteers does not reverse the retardation of gastric, small bowel or colonic transit induced by acute administration of codeine.